Spiritual Health and Emotional Intelligence of Nursing Students - Samson, Lyan Walt M.; Stojanovic, Kimberley Jan G.; Polancos, Jacqueline G.; Jael, Susy A.; Bingcang, Angel Grace F.; Sibayan, Ma. Julita SJ; Mergal, Beryl Ben C. (8ISC Abstract Proceedings, 2022)
Spiritual health and emotional intelligence status of nurses are important in the delivery of quality nursing care. A Descriptive-Correlational Comparative research design was used to determine the level of spiritual health and emotional intelligence (Self-control, Well-being, Emotionality, Sociability) of nursing students, the relationship of the variables, and the difference in the emotional intelligence when age, gender, and nationality were considered. Nursing students (N = 150) in seven (7) different sectarian schools in the Philippines were surveyed through purposive sampling. Results showed that the spiritual health and emotional intelligence of the respondents were high. There was a positive, significant relationship between spiritual health and emotional intelligence (p .000). The higher the level of spiritual health of the nursing students, the higher is the emotional intelligence. However, there was no significant difference in the emotional intelligence of the nursing students when gender, year level, and religion were considered. The results of the study supported the concepts in the Careful Nursing Values Model that emotional intelligence is deeply rooted in spiritual values and that spiritual value enforces emotional health. Based on the findings, it is important for nursing educators to create programs and activities that would enhance the spiritual health and emotional intelligence of the nursing students and for nursing students to participate in those activities. Future research studies should consider including other variables, increase the sample size and do a qualitative study to gain a deeper understanding of the phenomenon. Keywords : Spiritual Health, Emotional Intelligence, Self-control, Emotionality, Well-being, Sociability